A novel MIF signaling pathway drives the malignant character of pancreatic cancer by targeting NR3C2 - Yang, Shouhui; Gaida, Matthias; Bergmann, Frank (Cancer research, 2016)
Pancreatic cancers with aberrant expression of macrophage migration inhibitory factor (MIF) are particularly aggressive. To identify key signaling pathways that drive disease aggressiveness in tumors with high MIF expression, we analyzed the expression of coding and noncoding genes in high and low MIF-expressing tumors in multiple cohorts of pancreatic ductal adenocarcinoma (PDAC) patients. The key genes and pathways identified were linked to patient survival and were mechanistically, functionally, and clinically characterized using cell lines, a genetically engineered mouse model, and PDAC patient cohorts. Here, we report evidence of a novel MIF-driven signaling pathway that inhibits the orphan nuclear receptor NR3C2, a previously undescribed tumor suppressor that impacts aggressiveness and survival in PDAC. Mechanistically, MIF upregulated miR-301b that targeted NR3C2 and suppressed its expression. PDAC tumors expressing high levels of MIF displayed elevated levels of miR-301b and reduced levels of NR3C2. In addition, reduced levels of NR3C2 expression correlated with poorer survival in multiple independent cohorts of PDAC patients. Functional analysis showed that NR3C2 inhibited epithelial-to-mesenchymal transition and enhanced sensitivity to the gemcitabine, a chemotherapeutic drug used in PDAC standard of care. Furthermore, genetic deletion of MIF disrupted a MIF-mir-301b-NR3C2 signaling axis, reducing metastasis and prolonging survival in a genetically engineered mouse model of PDAC. Taken together, our results offer a preclinical proof of principle for candidate therapies to target a newly described MIF-miR-301b-NR3C2 signaling axis for PDAC management. Cancer Res; 76(13); 3838-50. ©2016 AACR.